Wireless monitoring system - Yaakub, Idris (2005)
Nowadays, wireless technology is used widely by so many users from government,private sector and even student. These technologies are use at office,café and KUKTEM. This technology are able to be used in any stage of ages.Even without had to plug the connection to any plug, user can connect to anywhere by having a Wireless Network Interface Card.User need connect to any access point and they are connected to the world without borders.Although it's so easy to be used, but it still had some problem where it came to the usages.It do not show any information on network usage in human readable and hard to understand whether display it in Kilobyte per second (KB/s),Kilobit per second (Kb/s), packet,error,average of usage, maximum of usage, and overall total of network usage.This will cause major problem when it came to security matters.It also can cause problem where some of the user used the bandwidth and cause a heavy traffic.With the monitoring tool that will be build, this problem can be solve when it came to some problem that aren't supposed to show up. This tool can give some power to the administrator to monitor the connection to network. This are hopefully can help to solve the problem.